PENGARUH KUALITAS PELAYANAN SAMSAT TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS KANTOR SAMSAT KOTA CIMAHI) - Manullang, Agnes Theresia; Vinny Stephanie Hidayat; Riki Martusa3 (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study aims to determine whether there is an effect of SAMSAT services on taxpayer compliance in paying motor vehicle taxes. This research is a case study. Data were obtained by conducting observations and questionnaires directly to taxpayers in SAMSAT Cimahi city. The sample used is 50 respondents. The data analysis technique used is data quality test, classical assumption test, and hypothesis testing. The results showed that service quality had an effect on taxpayer compliance based on the test results with the partial regression coefficient test (t test) obtained t count 2.787 with a value of Sig. 0.002. This means that the service quality variable partially affects taxpayer compliance